Analisis efisiensi perbankan syariah di Indonesia metode Stochastic Frontier Analysis - Lathiefah Rabbaniyah; Akhsyim Afandi (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
This study aims to analyse the efficiency of Islamic Banking in Indonesia during 2010 to 2016. Samples in this study consist of 8 sharia banks (BUS), 4 devisa banks and 4 non devisa banks. Stochastic Frontier Analysis (SFA) method is used to analyze data of this study with production function approach. The input variables are total fixed asset, total deposits, and operational cost. While the output variable is total financing of sharia bank. The result of study showed the highest efficient score by BUS devisa is BNI Syariah during 2015 period as 0,9981. The highest efficient score for BUS non devisa is BRI Syariah during 2010 period with 0,9998. Meanwhile, the lowest efficient score for BUS devisa is BNI Syariah during 2010 period with 0,8089, and the lowest efficient score for BUS non devisa is BCA Syariah during 2010 period with 0,7125.